Distinct metabolomic signatures in allergic rhinitis with concurrent chronic spontaneous urticaria: an untargeted metabolomics analysis reveals novel biomarkers and pathway alterations - Lyu, Xiaohong; Liu, Yi; Zheng, Huaijun; Li, Hongna; Wu, Zhoujie; Sun, Yi; Wu, Shanhong; Jiang, Xuehan; Wu, Shandong; Tang, Rui; Gao, Yue; Sun, Jinlyu (Frontiers in Immunology, 2025)
BackgroundAlthough allergic rhinitis (AR) and chronic spontaneous urticaria (CSU) share overlapping immunological pathways, their distinct clinical manifestations imply the involvement of unique underlying mechanisms. This study aimed to investigate the metabolomic differences between patients with AR alone and those with concurrent AR and CSU (AR_CSU, defined as patients simultaneously presenting with both conditions).MethodsAn untargeted metabolomic analysis was performed on serum samples from 53 AR patients and 14 AR_CSU patients using ultra-performance liquid chromatography coupled with high-resolution mass spectrometry (LC-MS/MS). Multivariate statistical analyses, including partial least squares-discriminant analysis (PLS-DA) and orthogonal partial least squares-discriminant analysis (OPLS-DA), were employed to identify differential metabolites and metabolic pathways.ResultsA total of 209 significantly different metabolites were identified between the AR and AR_CSU groups (p < 0.05). Distinct metabolic patterns were observed through PLS-DA and OPLS-DA analyses, with no overlap between the two groups. Twenty metabolites exhibited high diagnostic potential (AUC > 0.75), among which Fasciculic acid C and Biotin-XX-Hydrazide showed particularly strong discriminatory power (AUC ≈ 0.8). Pathway analysis highlighted significant alterations in linoleic acid, fatty acid, and arachidonic acid metabolism. Notably, fatty acid elongation pathways were upregulated in AR_CSU patients, whereas primary bile acid biosynthesis and Fc gamma R-mediated phagocytosis were downregulated.ConclusionsThis study represents the first comprehensive metabolomic comparison between AR and AR_CSU, identifying distinct metabolic signatures and potential biomarkers. These findings advance our understanding of the pathophysiological differences between these conditions and could inform the development of targeted therapeutic strategies.